2019
DOI: 10.1515/jpem-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

Improved adherence and growth outcomes with jet-delivered growth hormone

Abstract: Background We previously reported improved persistence and adherence to daily recombinant growth hormone (rGH) in children using jet transjection delivery compared to using needle-based devices. This study examines the relationship between improved adherence and medium-term growth outcomes in children receiving jet-delivered rGH (JrGH) at a single centre. Methods This was a retrospective longitudinal follow-up study of children (<16 years) treated with daily JrGH (somatropin; Ferring Pharmaceuticals) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…In the present study, the observed adherence rate was above 80% up to 3 years of clinical follow-up, which contrasts with the expected adherence rate of 55-65% observed in other studies using different r-hGH delivery technologies [22,23] and confirms the findings of other reports with the same methodology [5,6,13,14,24]. Additionally, this study suggests that adherence to therapy is predictor of clinical response, a factor that has been described in other scenarios where electromechanical auto-injectors are used to deliver drugs and to assess compliance to therapy [25−30].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, the observed adherence rate was above 80% up to 3 years of clinical follow-up, which contrasts with the expected adherence rate of 55-65% observed in other studies using different r-hGH delivery technologies [22,23] and confirms the findings of other reports with the same methodology [5,6,13,14,24]. Additionally, this study suggests that adherence to therapy is predictor of clinical response, a factor that has been described in other scenarios where electromechanical auto-injectors are used to deliver drugs and to assess compliance to therapy [25−30].…”
Section: Discussioncontrasting
confidence: 99%
“…The MPR and PDC were the most common RAMs reported (n = 19) [25][26][27][29][30][31][32][33]36,37,[39][40][41][42][43][44][45][46]55]. The RAMs used in eight other studies were equivalent to the proportion of days with medication supply, similar to MPR and PDC [21,22,34,[50][51][52][53][54].…”
Section: Measures Of Adherencementioning
confidence: 94%
“…The studies were conducted in 10 different countries, the majority (n = 33) of which were high-income countries, according to The World Bank definition [56]. These include the United States of America (n = 23) [21][22][23][24][25][26][27]29,[31][32][33][34][35]39,41,[47][48][49][50][51][52][53][54], United Kingdom (n = 3) [30,38,46], Israel (n = 2) [43,45], Taiwan (n = 1) [42], Korea (n = 1) [37], Australia (n = 1) [55], Netherlands (n = 1) [36], and Singapore (n = 1) [44]. Only two studies were conducted in upper-middle-income countries such as Brazil (n = 1) [28], and Malaysia (n = 1) [40].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations